Impact of Tungsten on Thermomechanically Induced Precipitation of Laves Phase in High Performance Ferritic (HiperFer) Stainless Steels - Jana Pöpperlová; Xiuru Fan; Bernd Kuhn; Wolfgang Bleck; Ulrich Krupp (Applied Sciences, 2020)
High-chromium ferritic stainless steels strengthened by Laves phase precipitates were developed for a high-temperature application in steam power plants. The impact of tungsten content on the precipitation of the intermetallic Laves phase during the newly developed thermomechanical process route was investigated. Due to rapid thermomechanically induced precipitation, a considerable reduction in processing time in comparison to the conventional solely thermal two-step processing of high chromium ferritic steels was achieved. Nevertheless, comparable mechanical properties at room temperature, i.e., the ultimate tensile strength of 712 MPa and the yield strength of 434 MPa, were obtained. The microstructure was analyzed by scanning electron microscopy (SEM) in combination with digital particle analysis, to estimate the particle size and the phase fraction of the Laves phase. The mean particle size of 52 nm and the volume fraction of 4.11% were achieved. Due to the tungsten content, an increase in the volume fraction and particle size was observed, giving rise to the higher strengthening effect.